Physiological effects of cold water immersion after exercices - Ionel, M.; Cristian, P.; Florin, T. D. (Science, Movement & Health, 2024)
Aim. The aim of the present study was to assess the effects of cold water immersion (CWI) after training on the recovery of physical performance, muscle damage, and muscle soreness in professional soccer players. At the same time, we want to investigate the benefits of water immersion in football, focusing on its potential to improve pain management and prevent injuries. Methods. We searched the following computerized databases: PubMed, Web of Knowledge, Google Scholar, and the websites of the Federation Internationale de Football Association (FIFA). The aim of this research was to specify the elements of recovery in football performance based on scientific studies and practical experience. Results. Some studies suggest that immediate immersion post-exercise is more beneficial, while others propose a delayed approach. Conclusions. Numerous studies have explored the effects of cold water immersion (CWI) in sports. Overall, CWI has been found to effectively reduce muscle soreness and accelerate recovery after intense exercise. It works by constricting blood vessels, reducing inflammation, and potentially minimizing muscle damage. However, there is some variability in individual responses, and the optimal timing and duration of CWI remain subjects of debate. While CWI appears promising for short-term recovery, its long-term impact on performance gains requires further investigation. Athletes and practitioners should consider individual preferences and the specific demands of their sport when incorporating CWI into their recovery strategies. Studies suggest that immediate post-macth immersion, ideally within the first hour, is more effective. The key aspects of procedure is water temperature, commonly ranging from 10 to 15 degrees Celsius, and immersion duration, often between 10 to 20 minutes.